2016
DOI: 10.1111/jog.13191
|View full text |Cite
|
Sign up to set email alerts
|

Safety of total laparoscopic hysterectomy in patients with prior cesarean section

Abstract: TLH in patients with a history of CS can be performed safely as such history had no effect on the major complication rate. Complications were rare and were treated successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…14,17,29,32,33 Ten of the remaining included studies assessed the odds of surgical complications following minimally invasive hysterectomy (laparoscopic-assisted vaginal hysterectomy, total laparoscopic hysterectomy, and roboticassisted hysterectomy) 16,[20][21][22][23]27,28,31,34,35 and 11 included studies assessed the odds of various types of hysterectomy including total abdominal hysterectomy and vaginal hysterectomy. 4,6,15,18,19,[24][25][26]30,36,37 Study designs of the included studies were cohort studies (24) 4,6,14-25,27-29,31-37 and case-control studies (two) 26,30 (Tables S3 and S4). Figure 2 shows the summary of the risk of biases stratified by the type of study design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,29,32,33 Ten of the remaining included studies assessed the odds of surgical complications following minimally invasive hysterectomy (laparoscopic-assisted vaginal hysterectomy, total laparoscopic hysterectomy, and roboticassisted hysterectomy) 16,[20][21][22][23]27,28,31,34,35 and 11 included studies assessed the odds of various types of hysterectomy including total abdominal hysterectomy and vaginal hysterectomy. 4,6,15,18,19,[24][25][26]30,36,37 Study designs of the included studies were cohort studies (24) 4,6,14-25,27-29,31-37 and case-control studies (two) 26,30 (Tables S3 and S4). Figure 2 shows the summary of the risk of biases stratified by the type of study design.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the summary of the risk of biases stratified by the type of study design. Quality assessment among 24 cohort studies using the Newcastle-Ottawa Scale indicated that high risks for comparability and outcome assessment were, respectively, noted in 15 [14][15][16][17][18][21][22][23][24][25]27,28,33,34,36 and 12 studies. 6,14,15,17,18,22,27,29,31,33,34,37 No cohort study was judged as having a high risk of selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…In cases with previous CS, surgeons often refrain from performing vaginal and laparoscopic hysterectomies for fear of increasing the complication rates. 12,13 In a recent cohort study, it was revealed that patients with a history of CS carried a greater risk of hysterectomies over the long term. Moreover, compared with patients who have…”
Section: This Study Was Completed With 505 Patients Using Yada-mentioning
confidence: 99%
“…, above average haemorrhage (5), low or high body mass index (5), placental adhesion disorder (4), concomitant surgery (4) and emergency procedure (2). Note that "surgeon inexperience or low volume" was self-defined by each study, and included undefined [28,34,49,50,59,62,77,78,93,96], a surgical trainee [97], a consultant with <8 years' experience [41] or having been primary operator for a given hysterectomy approach for fewer than 20 [23], 30 [40,82], 50 [43,87] or 100 cases [57].…”
Section: Risk Factors For Urological Injurymentioning
confidence: 99%